Analisis Kebijakan Wajib Swab PCR terhadap Kehadiran Peserta SKD CPNS Aceh Barat - Agus Pratama; Al Zuhri; Siti Jahria Sitompul; Nurasma Aripin; Nurhaslita Sari (Journal of Social and Policy Issues, 2022)
The Indonesian government in 2021 will reopen the recruitment of Civil Servant Candidates (CPNS) for the wider community. The implementation of the 2021 CPNS recruitment was carried out in the midst of the Covid-19 pandemic, so the government added requirements to take part in the Basic Competency Selection (SKD). The stipulation is that every SKD participant who will enter the exam room must show a PCR/Antigen Swab result with a negative Covid-19 result. This provision is a policy that must be obeyed by all CPNS participants who take part in the SKD. This policy received quite a variety of responses from SKD participants. Based on these facts, the purpose of this study is to find out the causes and relationship of the mandatory PCR/Antigen swab policy with the absence rate of 2021 CPNS participants from the 2021 CPNS SKD in West Aceh. The method used is descriptive analysis with a qualitative approach, with data collection techniques through in-depth interviews with participant informants who are absent from the SKD CPNS 2021. So that it can be used as a reference by the government in setting a policy in the future.